Recent Developments in Clinical Terminologies — SNOMED CT, LOINC, and RxNorm - Bodenreider, Oliver; Cornet, Ronald; Vreeman, Daniel J. (Yearbook of Medical Informatics, 2018)
Objective: To discuss recent developments in clinical terminologies. SNOMED CT (Systematized Nomenclature of Medicine Clinical Terms) is the world's largest clinical terminology, developed by an international consortium. LOINC (Logical Observation Identifiers, Names, and Codes) is an international terminology widely used for clinical and laboratory observations. RxNorm is the standard drug terminology in the U.S.Methods and results: We present a brief review of the history, current state, and future development of SNOMED CT, LOINC and RxNorm. We also analyze their similarities and differences, and outline areas for greater interoperability among them.Conclusions: With different starting points, representation formalisms, funding sources, and evolutionary paths, SNOMED CT, LOINC, and RxNorm have evolved over the past few decades into three major clinical terminologies supporting key use cases in clinical practice. Despite their differences, partnerships have been created among their development teams to facilitate interoperability and minimize duplication of effort.
Keywords: Vocabulary, controlled; Logical Observation Identifiers Names and Codes, RxNorm; Systematized Nomenclature of Medicine